Long‐Term‐Stable Strong Second Harmonic Generation in Flexible DAST−PVDF Composite Films Realized by the Interface Interactions. Issue 17 (13th August 2021) - Cheng, Xiaomeng; Xu, Xiangdong; Zhang, Mingang; Gu, Yu; Wang, Ququan; Qiu, Yunhang; Fan, Ting; Jiang, Yadong; Xu, Jimmy
Abstract: In this work, novel composite films that are composed of guest 4‐ N, N‐ dimethylamino‐4′ ‐N ′‐methyl‐stilbazolium tosylate (DAST) and host polyvinylidene fluoride (PVDF) polymer are prepared. Results show that these guest‐host composite films offer the advantages of strong second harmonic generation (SHG), scalability, flexibility, and long‐term stability. The SHG pumped at 800 nm in the poled, thermally annealed, and phase‐matched DAST−PVDF composite films are four orders of magnitude stronger than that of a pure PVDF film, or 300 times stronger than that of a potassium dihydrogen phosphate crystal. Particularly, the interface interactions of the electrostatic interactions and the strong intermolecular hydrogen bonds between DAST and PVDF improve the conjugation of π electrons and molecular ordering of DAST, making the NLO properties of the composites tunable with the ratio of DAST:PVDF. And consequently, the high SHG of the DAST−PVDF composite films can remain stable even after exposure to air for three years. Abstract : The dehydrations and ordered orientations of the DAST chromophores are induced by thermal annealing and electric poling, and particularly, the interface interactions of the electrostatic interactions and the intermolecular hydrogen bonds in the DAST–PVDF systems effectively restrict the mobilities of the aligned DAST chromophores, by which the flexible DAST–PVDF composite films exhibit long‐term‐stable strong SHG responses for three years.